Compliance policy as a manifestation of legal pluralism (Studia Prawnicze / The Legal Studies, 2018)
The aim of article is to describe the role of ‘compliance norms’, which functions as a preventive tool, also deters potential perpetrators of crimes and protects private entities from liability. Author analyzes the system of compliance norms in the context of compliance with criminal law as part of the phenomenon of legal pluralism.